1992
DOI: 10.1190/1.1443199
|View full text |Cite
|
Sign up to set email alerts
|

Radiation pattern and seismic waves generated by a working roller‐cone drill bit

Abstract: The seismic body wave radiation pattern of a working roller-cone drill bit can be characterized by theoretical modeling and field data examples. Our model of drill-bit signal generation is a pseudo-random series of bit-tooth impacts that create both axial forces and tangential torques about the borehole axis. Each drill tooth impact creates an extensional wave that travels up the drill string and body waves that radiate into the earth. The model predicts that P-waves radiate primarily along the axis of the bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…An additional pulse is also visible, particularly for z=30.0 m. This mode can be identified as a result of the propagation of conical waves (Meredith et al, 1993;Samec, 1991, Rector andHardage, 1992). This wave is the three-dimensional, axisymmetric space equivalent of a two-dimensional head-wave.…”
Section: Slow Formationmentioning
confidence: 89%
“…An additional pulse is also visible, particularly for z=30.0 m. This mode can be identified as a result of the propagation of conical waves (Meredith et al, 1993;Samec, 1991, Rector andHardage, 1992). This wave is the three-dimensional, axisymmetric space equivalent of a two-dimensional head-wave.…”
Section: Slow Formationmentioning
confidence: 89%
“…An additional pulse is also visible, particularly for z=30.0 m. This mode can be identified as a result of the propagation of conical waves (Meredith et al, 1993;Samec, 1991, Rector andHardage, 1992). This wave is the three-dimensional, axisymmetric space equivalent of a two-dimensional head-wave.…”
Section: Slow Formationmentioning
confidence: 97%
“…A couple of studies in oil and gas industries have proposed a technique called ''Seismic While Drilling'' for estimating rock formations. For instance, few studies have proposed the use of noise produced by the bit during drilling as a seismic source for surveying the area around a well and also for formation characterization while drilling [5][6][7][8][9][10][11][12][13][14]. A recent study [15] has also reported a method of estimating formation properties by analyzing acoustic waves that are emitted from and received by a bottom hole assembly.…”
Section: Introductionmentioning
confidence: 99%